Antimicrobial Properties of Elephantopus Scaber Against Crop Pathogenic Fungi - Nor Ain, binti Hussin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Harmful effect of synthetic fungicides towards environment and other organisms have become important issues nowadays. Research on the plant product to be developed as the alternative for synthetic fungicides has attracted interest of many scientists. Elephantopus scaber previously was reported to contain antimicrobial properties. The aim of this study is to determine the effect of antimicrobial properties of Elephantopus scaber against six crop pathogenic fungi viz., Glomerella cingulata, Fusarium oxysporum, F. solani, Pestalotiopsis sp, Colletotrichum sp and Pyricularia oryzae. 80% of methanols were used as solvent to extract the phytochemical content of E. scaber. Different concentrations of the methanol crude extracts were used in fungal growth inhibition test. Result showed methanol crude extract at 15% concentration retard the mycelia growth on four crop pathogenic fungi, P. oryzae, F. solani, G. cingulata and Colletotrichum sp. F. oxysporum and Pestalotiopsis sp. did not showed growth retardation at any concentration used.